Theodor Haecker and Alexander Dru: A Contribution to the Discovery of Kierkegaard in Britain - Heywood-Thomas, John; Siefken, Hinrich (KIERKEGAARDIANA, 1996)
Theodor Haecker and Alexander Dru: A Contribution to the Discovery of Kierkegaard in Britain